2023
DOI: 10.1007/s00066-023-02062-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of breathing-adapted 4D CT: image quality comparison to conventional 4D CT

Abstract: Purpose: 4D CT imaging is an integral part of 4D radiotherapy workflows. However, 4D CT data often contain motion artifacts that mitigate treatment planning. Recently, breathing-adapted 4D CT (i4DCT) was introduced into clinical practice, promising artifact reduction in in-silico and phantom studies. Here, we present an image quality comparison study, pooling clinical patient data from two centers: a new i4DCT and a conventional spiral 4D CT patient cohort.Methods: The i4DCT cohort comprises 129 and the conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…In the present study, an algorithm for optimized raw data selection in the presence of strong breathing irregularities aiming to improve image quality as well as geometric accuracy was evaluated. It seamlessly followed previous in-silico , phantom-based and clinical studies, which demonstrated a significant improvement in image quality with i4DCT compared to conventional algorithms [13] , [14] , [15] , [16] , [25] . Although 74% of the phantom [16] and 89% of the patient scans [25] were described as (nearly) artifacts-free with i4DCT compared to 13% and 25% with conventional algorithms, respectively, image artifacts still occurred in some cases, especially for single significant longer breathing cycles or breathing amplitudes < 50% of the reference cycle.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the present study, an algorithm for optimized raw data selection in the presence of strong breathing irregularities aiming to improve image quality as well as geometric accuracy was evaluated. It seamlessly followed previous in-silico , phantom-based and clinical studies, which demonstrated a significant improvement in image quality with i4DCT compared to conventional algorithms [13] , [14] , [15] , [16] , [25] . Although 74% of the phantom [16] and 89% of the patient scans [25] were described as (nearly) artifacts-free with i4DCT compared to 13% and 25% with conventional algorithms, respectively, image artifacts still occurred in some cases, especially for single significant longer breathing cycles or breathing amplitudes < 50% of the reference cycle.…”
Section: Discussionsupporting
confidence: 60%
“…It seamlessly followed previous in-silico , phantom-based and clinical studies, which demonstrated a significant improvement in image quality with i4DCT compared to conventional algorithms [13] , [14] , [15] , [16] , [25] . Although 74% of the phantom [16] and 89% of the patient scans [25] were described as (nearly) artifacts-free with i4DCT compared to 13% and 25% with conventional algorithms, respectively, image artifacts still occurred in some cases, especially for single significant longer breathing cycles or breathing amplitudes < 50% of the reference cycle. For radiation protection reasons, a scan is currently stopped at a distinct z -position when reaching a maximum scan time t max , resulting in insufficient information for image reconstruction.…”
Section: Discussionsupporting
confidence: 60%
“…An alternative is optical or IR tracking applied many times in radiotherapy, e.g. for patient positioning at the linear accelerator [40][41][42] or four-dimensional CT. 43,44 For interventions and surgery, such tracking was also already used for (pre-)clinical investigations. [45][46][47] However, corresponding approaches are mainly based on external tracking cameras that would again require a tracking of both CBCT scanner and actual marker tool to establish a position transfer, concomitant with increased inaccuracies of up to >2 mm reported.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative is optical or IR tracking applied many times in radiotherapy, e.g. for patient positioning at the linear accelerator 40–42 or four‐dimensional CT 43,44 . For interventions and surgery, such tracking was also already used for (pre‐)clinical investigations 45–47 .…”
Section: Discussionmentioning
confidence: 99%